2002
DOI: 10.1074/jbc.m201681200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neuropilin-1 Structural Features That Confer Binding to Semaphorin 3A and Vascular Endothelial Growth Factor 165

Abstract: Neuropilin-1 (Npn-1) is a receptor for both semaphorin 3A (Sema3A) and vascular endothelial growth factor 165 (VEGF 165 ). To understand the role Npn-1 plays as a receptor for these structurally and functionally unrelated ligands, we set out to identify structural features of Npn-1 that confer binding to Sema3A or VEGF 165 . We constructed Npn-1 variants containing deletions within the "a" A complex but ordered series of axon guidance decisions during development is critical for the establishment of nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
226
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(237 citation statements)
references
References 40 publications
6
226
2
Order By: Relevance
“…10 Thus, while Nrp-1 expression may be required for Sema3A and VEGF-mediated VP, it appears that Nrp-1 may differentially induce VP by distinct pathways in response to Sema3A or VEGF due to distinct binding sites for VEGF and Sema3A on Nrp-1. 32 Previous studies revealed that inhibition of the Src family kinases Src or Yes through genetic ablation or a pharmacological inhibitor blocked the VP in response to VEGF and protected mice from tissue damage after myocardial infarction or stroke. [12][13][14] To shed light on the mechanism by which Sema3A induces VP, mice were systemically treated with a Src inhibitor SKI-606 and then challenged with subcutaneous injection of Sema3A or VEGF.…”
Section: Resultsmentioning
confidence: 99%
“…10 Thus, while Nrp-1 expression may be required for Sema3A and VEGF-mediated VP, it appears that Nrp-1 may differentially induce VP by distinct pathways in response to Sema3A or VEGF due to distinct binding sites for VEGF and Sema3A on Nrp-1. 32 Previous studies revealed that inhibition of the Src family kinases Src or Yes through genetic ablation or a pharmacological inhibitor blocked the VP in response to VEGF and protected mice from tissue damage after myocardial infarction or stroke. [12][13][14] To shed light on the mechanism by which Sema3A induces VP, mice were systemically treated with a Src inhibitor SKI-606 and then challenged with subcutaneous injection of Sema3A or VEGF.…”
Section: Resultsmentioning
confidence: 99%
“…The EC domain consists of two CUB calcium-binding homology domains (a1 and a2), two coagulation factor V and VII homology domains (b1 and b2) and a MAM (meprin) domain (c) critical for receptor dimerization. The b1/b2 and a1/a2 domains mediate the high-affinity binding of NRPs to their ligands – the VEGFs and the class 3 semaphorins 62 . The NRP cytoplasmic domain has 40 residues and allows binding of the PDZ domain-containing protein GIPC1 (or synectin) 49 .…”
Section: Vegf-a Isoforms Exhibit Differential Binding To Vegfrs and Nrpsmentioning
confidence: 99%
“…The CUB designation originates from the original three proteins identified with the motif: complement subcomponents (C1r/C1s), embryonic sea urchin protein (Uegf), and bone morphogenic protein 1 (Bmp1). CUB domains are thought to play roles in adhesion proteins, such as the galectins, DMBT1 (23), sperm adhesin (22), and neuropilin (24), and proteases including Bmp1/C-proteinase, tolloid, and MASP (16). gp140/p80 is encoded by the CDCP1 gene, which is elevated in human lung and colon tumors.…”
Section: Discussionmentioning
confidence: 99%